Implementasi Revitalisasi Komunikasi Pembangunan Berkelanjutan Pada Branding Cultural Heritage Traildi Desa Trowulan, Kabupaten Mojokerto: Ditinjau Dari Teori Coordinated Management of Meaning - Mokhamad Yunus; Nurma Yuwita (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This research uses descriptive qualitative research with the method of Sustainable Development Communication and Coordinated Management of Meaning Theory which aims to find out how the implementation of sustainable development communication revitalization on cultural heritage trail branding in Trowulan Village, Mojokerto Regency with the CMM theory approach. The Coordinated Management of Meaning theory provides a strong foundation for analyzing and implementing effective communication in cultural heritage branding efforts in Trowulan Village. This theory not only helps to understand complex communication dynamics, but also provides tools to effectively manage and coordinate meaning in the context of sustainable development.Thus, this research is expected to obtain the result that the implementation of revitalization of sustainable development communication has an important role in tourism development in Trowulan Village, especially in Branding Cultural Heritage Trail which is contained in the CMM theory.